Robotics Research 1996
DOI: 10.1007/978-1-4471-1021-7_28
|View full text |Cite
|
Sign up to set email alerts
|

A Random Sampling Scheme for Path Planning

Abstract: Several randomized p ath planners have been proposed during the last few years. Their attractiveness stems from their applicability to virtually any type o f r obots, and their empirically observed s u c cess. In this paper we attempt to present a unifying view of these planners and to theoretically explain their success. First, we introduce a general planning scheme that consists of randomly sampling the robot's con guration space. We then describe t w o p r eviously developed planners as instances of planner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 30 publications
0
52
0
2
Order By: Relevance
“…It is shown that both PRM and RRT are complete [24,25]. This implies that th successfully return a solution provided one this probabilistic completeness is guar approaches infinity.…”
Section: Introductionmentioning
confidence: 89%
“…It is shown that both PRM and RRT are complete [24,25]. This implies that th successfully return a solution provided one this probabilistic completeness is guar approaches infinity.…”
Section: Introductionmentioning
confidence: 89%
“…Other approaches, such as randomization [11] and sampled-based techniques [12], compute a feasible path to reach a desired location by interconnecting a number of randomly generated intermediate states [13], [14]. However, as a main drawback, they can be employed only for stationary environments where the position of obstacles is known a priori.…”
Section: A Backgroundmentioning
confidence: 99%
“…The corresponding discretized chain postures are denoted as . The combination of one posture from each of the chains constitutes a discretized robot configuration , that is (2) There are discretized configurations, , where…”
Section: A Robot Decompositionmentioning
confidence: 99%
“…These basic strategies have been modified in the past decade creating the randomized methods among others, which have made faster path planning possible [2]. Probabilistic road map methods [17], [18] model the environment off-line by a random set of collision-free configurations generated in the learning phase according to the local complexity of the environment.…”
mentioning
confidence: 99%